(untitled) (Jurnal Geomine, 2021)
Tolangohula is one of the prospects situated within gold and base metal mineralization belt of North Sulawesi, which is administratively a part of Limboto Regency, Gorontalo Province. Exploration data or studies within the prospect is scarce, therefore, this study was conducted aiming at understanding of the geological conditions, the distribution of the alteration zone and ore mineralization, as well as the rock / ore geochemistry to delineate the recommended target areas for further detailed exploration. Research methods include surface mapping of detailed geology and alteration zone, sampling and sample analyses by petrography, ore microscopy and ore geochemistry using FA-AAS and ICP-MS. Geochemical data were treated using univariate and multivariate analyses. The study area is occupied by andesite, which is intruded by diorite-granodiorite, a member of Middle-Late Miocene Boliohuto Diorite (Tmbo). Geological structures are developed in relatively northeast-southwest and northwest-southeast direction. Hydrothermal alteration is identified as phyllic, argillic and propylitic types. Phyllic zone reveals a pervasive alteration, which is closely associated with the occurrences of vein/veinlet stockwork. Ore mineralization is mostly in form of disseminated and vein/veinlet, which is characterized by bornite, chalcopyrite, pyrite, magnetite and free gold. Gold content ranges from <0.005 ppm to 0.363 ppm with an average of 0.028 ppm. Copper content varies from <2 ppm to 1,830 ppm (0.183%), with an average of 189.5 ppm. Cu and Au grade has a positive correlation. High Au and Cu is associated with strong mineralization/alteration zone (i.e phyllic alteration). Based on those characteristics, the deposit in the study area is possibly of porphyry Cu-Au type. Moreover, three target areas are recommended for next follow-up exploration including Target Area 1 (East Block), Target Area 2 (Middle Block) and Target Area 3 (West Block). Soil geochemistry as well as IP and/or ground magnetics surveys are recommended for the target areas.